1991
DOI: 10.1111/j.1365-2273.1991.tb01050.x
|View full text |Cite
|
Sign up to set email alerts
|

Sleep nasendoscopy: a technique of assessment in snoring and obstructive sleep apnoea

Abstract: It appears that uvulopalatopharyngoplasty (UVPP) is a reliable procedure for reducing snoring, but much less reliable when used as a treatment for OSAS. This is thought to be because of poor patient selection in that the site of the problem is not always the site of the operation. We present the technique of sleep nasendoscopy which allows direct visualization of the site or sites of obstruction in a sleeping patient. Our study has shown that there are patients with obstructive sleep apnoea syndrome (OSAS) in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
214
0
16

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 415 publications
(233 citation statements)
references
References 18 publications
3
214
0
16
Order By: Relevance
“…First described in 1991, the technique requires the pharmacologic induction of sleep and the placement of a flexible fiberoptic telescope (passed through the nose) to visualize the upper airway 8, 9. This provides an opportunity to observe directly and characterize the upper airway collapse that occurs during drug-induced sleep.…”
Section: Introductionmentioning
confidence: 99%
“…First described in 1991, the technique requires the pharmacologic induction of sleep and the placement of a flexible fiberoptic telescope (passed through the nose) to visualize the upper airway 8, 9. This provides an opportunity to observe directly and characterize the upper airway collapse that occurs during drug-induced sleep.…”
Section: Introductionmentioning
confidence: 99%
“…Sleep endoscopy was first described in 1991 by Croft and Pringle [12]. Since then, many studies have shown sleep endoscopy to be a safe and useful tool in the evaluation of the upper airway obstruction [1416].…”
Section: Discussionmentioning
confidence: 99%
“…Sleep endoscopy has been previously described in the adult and pediatric populations for the purpose of evaluating the dynamic airway in the supine position during a sleep-like state [6, 12, 13]. It is an increasingly useful tool in the evaluation of children with persistent OSA after initial therapy, children with OSA without tonsil or adenoid hypertrophy, or children with significant craniofacial anomalies.…”
Section: Introductionmentioning
confidence: 99%
“…Accurately identifying the main source of snoring sound is important for surgical success [9]. DISN was first described by Croft and Pringle [10] in 1991, and this procedure allows a direct visualization of the sites of vibration or obstruction in a sleeping patient. Compared with the routine clinical examinations while the patient is awake, DISN is considered to be of special value in upper airway evaluation and treatment selection for patients with either SS or OSAS.…”
Section: Discussionmentioning
confidence: 99%